An Analysis Of Automatic Function Smoke Detection Tools Based On Arduino Uno - David Siringoringo; Zuraidah Tharo; Parlin Siagian (Jurnal Scientia, 2024)
In the era of the industrial revolution, the use of technology to increase safety and efficiency in various fields is increasingly growing. One important application is an automatic smoke detection system that can prevent fires effectively. This paper described an analyze the performance of an Arduino Uno-based automatic smoke detection tool which can turn the system on and off automatically. This tool is designed to detect the presence of smoke using the MQ-2 sensor and provide a response in the form of activating the alarm and fire extinguishing system.This system consists of several main components: an MQ-2 sensor to detect smoke, an Arduino Uno microcontroller as the main controller, a relay module to control external devices, and a buzzer alarm as a fire indication. When the sensor detects smoke, the data is sent to the Arduino Uno which then processes the signal and activates the alarm and fire extinguishing system via the relay module, also evaluates the effectiveness and reliability of the smoke detection system by conducting a series of trials in various environmental conditions. The test results show that this tool is able to detect smoke quickly and accurately, and provide a timely response in activating the security system. The system can be set to turn devices on and off automatically, increasing efficiency and reducing the risk of human error.